PENGARUH DESKRIPSI KERJA (JOB DESCRIPTION), WORK-LIFE BALANCE DAN BUDAYA KERJA TERHADAP KEPUASAN KERJA PEGAWAI PERPUSTAKAAN DAERAH PROVINSI SUMATERA SELATAN - Shelly Nurillah Sucaga; Ulil Amri; Mariyam Zanariah (Fakultas Ekonomi Universitas Tridinanti Palembang, 2018)
This study examines the Influence of Job Description, Work-LifeBalanceAnd Work Culture Against Job Satisfaction Employees Regional Library of South Sumatra Province. Implementation of research for 5 (five) months including in designing, executing and reporting result of research.This case study research aims to find out the influence of Job Description, Work-Life Balance And Working Culture either partially or collectively to Satisfaction of Employees of Regional Library of South Sumatera Province. In this study the population in question is the Employee In the Regional Library of South Sumatra Province, with the number of 70 people. From the result of this research there is influence of Job Description, Work-Life Balance And Work Culture with regression model ŷ = 14,741 + 0,283X1 + 0,756 X2 + 0,212 X3 + e. The three independent variables are mutually run along with the dependent variable means the higher Job Description, Work-Life Balance And Work Culture the higher the job satisfaction. Work-Life Balance variables are more influential on job satisfaction. From the results of computer calculations, showed the coefficient of determination (R2) obtained value of 0.681 or equal to 68.10%, while Adjusted (R2) of 0.644 or 64.40%. Variations in job satisfaction are explained by Job descriptions, work-life balance and Work culture. While the remaining amount (100% - 64.40% = 35.60%) is explained by other factors not examined. Implementation is an effort to improve job satisfaction of Regional Library Employees of South Sumatera Province can also be done through a clear understanding of job description, the role of each employee in the ability to balance between task and family (Work-life Balance) and improvement of work culture. Efforts that need to be done to improve job satisfaction of Regional Library Employees of South Sumatra Province. Keywords: job description, work-life Balance, work culture